Problems of urban development planning - Klaus Grimm (Intereconomics, 1976)
In developing countries the urbanisation process poses one of the most serious problems, for it creates unemployment, utmost poverty and aggravates the general situation. In this article the case of indonesia is discussed and possible strategies for a future improvement of such a situation are pointed out.
Keywords: 330; Indonesia